Community Empowerment through Natural Coloring Batik Entrepreneurship - Endah Nurhawaeny Kardiyati (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2025)
The development of community empowerment through natural coloring batik entrepreneurship has a positive impact on local communities, especially batik artisans. However, the insights and knowledge of batik artisans and consumers have not been built in totality, especially in terms of reading sources about community empowerment and batik entrepreneurship. The purpose of this research is to contribute insights and readings about community empowerment and natural coloring batik entrepreneurship both in terms of authors, volume, and networking. This research uses the literature review research method which will be made will discuss entrepreneurship in the use of natural coloring in batik. This literature review will focus on the use of natural dyes in the batik industry, exploring various previous studies relevant to this theme. The results show that (1) The community and entrepreneurship of batik coloring are already quite a lot, it's just that there are still minimal readers. (2) Data on volume and journals also show that the more relevant the journal is, the more it is published. (3) The network between authors shows that community empowerment is very interesting to research so as to get an article that can be developed in the community. Meanwhile, the implication of the systematic literature review research on community empowerment and natural coloring batik entrepreneurship is that it adds insight into writers, observers, academics, and practitioners regarding community empowerment and its volume and network.